Application of Slags from Thermal Power Station as an Effective Initial Material in the Production of Artificial Porous Filler - D. Huseyn Mammadov, Ph.; Gadirov, Musa (International Journal of Engineering and Technology, 2018)
The article is devoted to obtaining an artificial porous filler from industrial wastes, in particular from granulated slags, or ash-slag mixtures from Thermal Power Station. The developed technology provides the opportunity to expand the raw material base of artificial porous filler production for lightweight concrete, and it allows us to solve the problem of involving secondary resources in the production of construction materials and protection of the environment from pollution.According to the results of research, the intervals of the bloating temperature have been determined, the technology of obtaining an artificial porous filler from slag and ash-slag mixtures from Thermal Power Station has been developed, and the mainphysical-mechanical properties of the filler obtained have been studied. It was established that the obtained artificial porous filler meets the requirements of the current standard in its physical-mechanical properties. It was found that on the basis of them, heat-insulating, heat-insulating-constructional and structural lightweight concrete for enclosing and bearing constructions have been obtained.Â Â